DEVELOPMENT OF A MODEL OF TEACHERS' ORGANIZATIONAL COMMITMENT AS AN EFFORT TO STRENGTHEN SUSTAINABLE PROFESSIONALISM - Astuti, Siwi Puji; Setyaningsih, Sri; Wulandari, Dian (International Journal of Multidisciplinary Research and Literature, 2025)
This study aims to examine a model of teachers' organizational commitment by conducting surveys and field observations related to the factors influencing teachers' organizational commitment. In the qualitative phase, which involved interviews and focus group discussions (FGDs) with teachers and school principals, the researcher developed a research constellation model consisting of three independent variables: psychological empowerment, authentic leadership, and interpersonal communication. The intervening variable is pedagogical competence. The research employed a mixed-methods approach, with qualitative research used to explore the variables in the field and quantitative research used to test the constructed model. The sample consisted of 160 civil servant teachers teaching at 15 public junior high schools (SMP Negeri) in region 2 of East Jakarta. The model was tested using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results showed that the R² value was 0.927, indicating that 92.7% of the variance in teachers' organizational commitment could be explained by the variables in the model. The dominant contributions came from psychological empowerment and pedagogical competence. The Q² value was 0.621, which is greater than 0.05, suggesting that the exogenous variables X1, X2, and X3 are appropriate and relevant predictors for the endogenous construct X4. The Goodness of Fit (GoF) analysis showed an SRMR value of less than 0.08 (under 0.1), indicating that the tested model fits the data well. Additionally, the PLS Predict analysis revealed that the Q²_predict values from the PLS model were higher (8) than those from the linear model (LM), which had only 2. Therefore, it can be concluded that the model has a strong predictive power.